Policing Policy General Order 13-04: Detainer Policy - (:unkn) unknown (My University, 2013)
A Newark Police Department Director's Memorandum dictating that the Newark Police Department will not comply with Immigration and Customs Enforcement (ICE) detainer requests.
Keywords: Sanctuary Policies